Duration as an axiology of the political ethology in Spinoza - Vinolo, Stéphane (Revista de Filosofía, 2018)
The problem of evaluation in politics is no less than the one of quantifying qualities. In order to evaluate the opportunity of political regimes or governments, one must be able to find a common factor thanks to which one will be able to compare them from an objective point of view. In the immanent political philosophy of Spinoza, this common factor is duration. Therefore, we can understand how Spinoza has been able to affirm democracy as the absolute regime, non-because it promotes absolute and definitive values, but on the contrary, because democracy, due to its inherent rationality, last much more than any other regime.